Using ChatGPT for Identifying Negative Structures in Social Media Conversations - Tölle, Laura; Nolting, Max; Trier, Matthias

Method for systematic creation of test scenarios for early customer involvement - Gräßler, Iris; Ebel, Marcel; Pottebaum, Jens (Procedia CIRP)
Verification planning for engineering complex systems lacks a systematic procedure for creating test scenarios. Test scenarios can be generated by combining test cases, or by integrating test cases into pre-specified scenarios. Based on a systematic literature analysis a method is developed to simplify verification planning by creating new test scenarios and enriching existing ones. To assist the V&V engineer in planning test scenarios, a catalogue of combination premises is created to support the method. The method is evaluated in the development of a platform for emergency management. Evaluation proves that the method makes modelling of test scenarios more efficient.
Keywords: Systems Engineering; test scenario creation; verification; customer involvement

Ganzheitliches Metadatenmodel für die Verifikation und Validierung in der Entwicklung komplexer technischer Systeme - Gräßler, Iris; Ebel, Marcel (DS 140: Proceedings of the 36th Symposium Design for X (DFX2025))
The increasing complexity of technical systems requires early, structured verification and validation (V&V). Existing metadata models only map parts of the engineering process and do not enable a continuous chain of effects from requirements to test results. The aim of this publication is to develop a holistic V&V metadata model for the consistent, transparent and machine-processable description and linking of relevant engineering artifacts. In a five-stage research approach, essential model components are derived from literature and are integrated into a holistic model. Initial applications as part of a European research project show the potential of the model for a well-founded effect chain analysis and decision-supporting V&V processes.
Keywords: verification; metadata model; Systems Engineering

Augmented Reality for Navigation, Team Coordination, and Real-Time Data Visualization in Firefighting Operations - Charalampakis, Konstantinos; Safranoglou, Ioannis; Stavroulakis, Alexis; Ebel, Marcel; Gräßler, Iris; Dimelli, Despina; Mania, Katerina (2025 IEEE International Symposium on Mixed and Augmented Reality Adjunct (ISMAR-Adjunct))

Thermo-Chemical Devulcanization of Sulfur-Cured Styrene-Butadiene Rubber (SBR) Using Diphenyldisulfide (DPDS) - Petzke, Jonas Dirk Rudolf Helmut; Schöppner, Volker

Symmetry as a Topic for the University Education of Pre-Service Teachers - Hoffmann, Max (Recherches en Didactique des Mathématiques)
This article provides a comprehensive mathematical-didactic analysis of how the highly relevant topic symmetry can be prepared for the university education of PSTs. Methodologically, the analysis is embedded in a design research cycle and serves as preparation for the actual design of learning activities. The procedure of "specifying and structuring" learning objects is used and adapted in such a way that, in addition to mathematical aspects, profession-oriented references to school mathematics are also considered. An essential result of the analysis is the formulation of so-called interface aspects to symmetry, which prove to be helpful in establishing such references.

Influence of Filler Type and Volume Fraction on the Electrical Conductivity and Shore Hardness of TPU Composites in Fused Filament Fabrication - Moritzer, Elmar; Salm, Maximilian Karl Franz (The 40th International Conference of Polymer Processing Society)

Using scriptwriting as a response format for interface tasks: Exemplary analyses in the context of symmetry - Hoffmann, Max (Proceedings of the Fourteenth Congress of the European Society for Research in Mathematics Education (CERME14))

Non-destructive fiber-matrix adhesion measurement of glass fiber reinforced thermoplastic composite laminates using ultrasound - Moritzer, Elmar; Brandes, Philipp; Wittler, Maurice; Claes, Leander; Wippermann, Mareen; Henning, Bernd (40th International Conference of the Polymer Processing Society)
Keywords: Faser-Kunststoff-Verbunde (FKV); Faserverstärkte Kunststoffe (FVK); Organobleche; Ultraschall

Experimental Analysis of the Mixing Behavior of Ethylene-Propylene-Diene Rubber (EPDM) in a Rubber Pin Extruder under Variation of Process Parameters and Mixing Elements - Petzke, Jonas Dirk Rudolf Helmut; Schmidt, Leon; Kleinschmidt, Dennis; Brüning, Florian (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: distributives Mischen; Extrusion; Kautschuk; Stiftextruder

Numerical modeling of the non-isothermal viscoelastic flow behavior of rubber compounds based on the PHAN-THİEN-TANNER (PTT) model - Damanik, Hogenrich; Fatima, Arooj; Turek, Stefan; Petzke, Jonas Dirk Rudolf Helmut; Kleinschmidt, Dennis; Brüning, Florian (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: CFD simulation; Materialmodellierung; Phan-Thien-Tanner; PTT; Simulation

Thermo-Chemical Devulcanization of Sulfur-cured Styrene-Butadiene Rubber (SBR) Using Diphenyldisulfide (DPDS) - Petzke, Jonas Dirk Rudolf Helmut; Kleinschmidt, Dennis; Brüning, Florian (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: Devulkanisation; Kautschuk; Recycling

Investigations into the specific throughput stability of conical feed zones over the rotation speed during the direct processing of polypropylene regrind - Rempel, Timm; Brüning, Florian (ANTEC)

Devulcanization behavior of SBR-based GTR compounds - Petzke, Jonas Dirk Rudolf Helmut

Differences of producing head fakes with and without a social partner - Böer, Nils Tobias; Güldenpenning, Iris; Weigelt, Matthias (67th Conference of Experimental Psychologists)
Keywords: deception; action preparation; perception; movement planning; sport psychology

High-Speed Mach-Zehnder Modulator with Linear Segmented On-Chip Drivers in Photonic 45nm SOI-CMOS Technology - Kress, Christian; Schwabe, Tobias; Mihaylov, Martin Miroslavov; Scheytt, J. Christoph
We present an electronic-photonic co-designed Mach-Zehnder modulator with linear segment drivers in a photonic SOI-CMOS technology with an EO 3-dB bandwidth of ≥ 27 GHz and data transmission up to 64 Gbit/s without pre-emphasis.

Quantum resonances and scattering poles of classical rank one locally symmetric spaces - Delarue, Benjamin; Hilgert, Joachim (Journal of Lie Theory)
For negatively curved symmetric spaces it is known that the poles of the scattering matrices defined via the standard intertwining operators for the spherical principal representations of the isometry group are either given as poles of the intertwining operators or as quantum resonances, i.e. poles of the meromorphically continued resolvents of the Laplace-Beltrami operator. We extend this result to classical locally symmetric spaces of negative curvature with convex-cocompact fundamental group using results of Bunke and Olbrich. The method of proof forces us to exclude the spectral parameters corresponding to singular Poisson transforms.

Digitale Ressourcen im Psychologieunterricht - Brucks , Tabea; Buhl, Heike M. (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen. Ein Lehrbuch mit Unterrichtsmaterialien)

DART - Datengetriebene Methoden in der Regelungstechnik - Timmermann, Julia; Götte, Ricarda-Samantha; Junker, Annika; Hesse, Michael; Schwarzer, Luis
Im Zuge der Digitalisierung erfahren maschinelles Lernen und datengetriebene Methoden derzeit eine große Aufmerksamkeit in Wissenschaft und Industrie. Es fehlt jedoch an Grundlagenwissen und Verständnis, wie die datengetriebenen Methoden der Informatik mit bewährten modellbasierten Ingenieursmethoden wie dem modellbasierten Entwurf in der Mechatronik und Methoden der Regelungstechnik sinnvoll kombiniert werden können, um hybride Modelle zu erhalten. Diese ingenieurwissenschaftlichen Methoden basieren auf physikalischen Verhaltensmodellen, die eine besonders verdichtete und interpretierbare Darstellung von Wissen darstellen und insbesondere kausale Zusammenhänge beschreiben. Für spezifische regelungstechnische Anwendungen gibt es umfangreiches Vorwissen in Form von bekannten Strukturen und Informationen, wie z.B. (Teil-)Modelle oder Parametersätze, die auch bei der Anwendung von Methoden wie dem maschinellen Lernen genutzt werden sollten. Eine solche sinnvolle systematische Verknüpfung ist wissenschaftlich, insbesondere im Hinblick auf die industrielle Anwendung, noch nicht ausreichend untersucht worden und sehr vielversprechend. In diesem Beitrag werden die Ergebnisse der Nachwuchsforschungsgruppe DART – Datengetriebene Methoden in der Regelungstechnik vorgestellt. Das Hauptziel war es, die synergetische Kombination von modell- und datengetriebenen Methoden für regelungstechnische Aufgaben zu erforschen und es werden alle wichtigen Forschungsergebnisse aber auch die verwendeten Grundprinzipien des maschinellen Lernens in diesem Beitrag dargestellt.

Blockchain‑based reputation systemsfor business‑to‑business services: designing a reputation mechanism to reduce information asymmetry in professional consulting - Hemmrich, Simon; Nissen, Volker; Beverungen, Daniel; Pauls, Josias Daniel Miño (Information Systems and e-Business Management)
Reputation systems to rate companies’ performances remain largely unexplored inresearch and are scarcely used in business-to-business (B2B) practice. Such systemsare essential for businesses seeking trustworthy partners, as they help reduce infor-mation asymmetry, lower buyers’ transaction risks, and allow high-quality serviceproviders to justify premium pricing. Unlike traditional review-based systems in thebusiness-to-consumer (B2C) context, we propose a B2B reputation mechanism inwhich buyers commit to a rating payment before a transaction. Once the buyer final-izes the rating, this payment is executed and recorded on a blockchain as an immu-table, secure ledger. Our system mimics natural trust-building mechanisms with rat-ings that are (1) monetary-based, (2) stake-based, (3) non-aggregated, (4) involvecounter-ratings, (5) selectively sellable, (6) individually comparable, (7) stored ona blockchain, (8) and monitored by a third instance. This system provides a novelapproach to fostering trust in B2B transactions by reducing information asymme-try and transaction risk. We illustrate the mechanism’s application in the consultingsector. Our analysis has identified 23 institutional trust and distrust dimensions thatpromote establishing institutional trust through the proposed mechanism. Qualita-tive interviews suggest that, while complex and challenging to apply, this mecha-nism can foster trust in B2B transactions. Given the low maturity in the applicationdomain—rating professional business services with business reputation systems—and solution domain—using monetary stakes for ratings, this system stands as apotential invention.
Keywords: Information asymmetry; Trust; Reputation system; Monetary rating; Blockchain; Consulting